Pensions in the Middle East and North Africa: Time for Change - Robalino, David (Washington, DC: World Bank, 2012)
This is the first comprehensive assessment of pension systems in the Middle East and North Africa. While other regions-Central Asia, Eastern Europe, and Latin America, in particular-have been actively introducing reforms to their pension systems, Middle East and North African countries have lagged behind. This is explained, in part, by the common belief that, because demographics remain favorable-the countries are young and the labor force is expanding rapidly-financial problems are far in the future; as a result, pension reform does not have to be a priority in the broader policy agenda. However, the authors show that aging is not the only factor behind a financial crisis; the problem is the generosity of the current schemes. Moreover, badly designed benefit formulas and eligibility conditions introduce unnecessary economic distortions and make the systems vulnerable to adverse distributional transfers. The book does not present a general model that could solve the problems of all pension systems in MENA countries. Instead the authors focus on outlining a framework for guiding discussions on pension reform and making objective policy choices.